Tuntutan Kerja di Era Always-On: Analisis Job Demand sebagai Faktor Pemicu Burnout - Dharmawan, Stephanus Raymond; Zamralita, Zamralita (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2025)
The acceleration of digital transformation has fostered an always-on work culture in which employees are expected to remain continuously connected and responsive beyond formal working hours. This condition has blurred the boundaries between work and personal life and poses serious risks to employees’ psychological well-being. This study aimed to examine the role of job demands in the development of burnout among employees working within a continuous connectivity work culture in Jakarta. A quantitative, non-experimental design was employed. Data were collected from 133 employees working in various companies in Jakarta using the Burnout Assessment Tool (BAT) and the Job Demands–Resources Questionnaire (JD-R). Descriptive analysis indicated that both perceived job demands and burnout levels were relatively high among participants. Pearson correlation analysis revealed a significant positive relationship between job demands and burnout (r = 0.414, p < 0.001). This relationship was further confirmed through linear regression analysis, which showed that job demands significantly predicted burnout (F = 27.045, p < 0.001), explaining 17.1% of the variance in burnout (R² = 0.171). Additional analysis demonstrated that job demands had the strongest influence on the emotional impairment dimension of burnout compared to other dimensions. These findings indicate that increasing work pressures, particularly in digitally driven environments that require constant availability, substantially elevate the risk of burnout among employees. The study reinforces the Job Demands–Resources model, emphasizing that excessive job demands without sufficient resources contribute to employee exhaustion and emotional impairment. The results highlight the urgent need for organizations to implement sustainable work management strategies, such as regulating after-hours connectivity and promoting work–life balance, to protect employees’ mental health in the era of digital work.